Distribution Pattern Environmental Sanitation Analysis and Diarrhea with Stunting Incidence in Toddlers in Karo Regency North Sumatra Province - Jernita Sinaga; Risnawati Tanjung; Restu Auliani; Deli Syaputri (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Stunting is a national problem because its increasing prevalence and impact can increase less competitive human resources, affect work productivity, increase the risk of overweight and obesity, and trigger metabolic syndrome. Environmental factors such as sanitation and hygiene, drinking water sources, drinking water quality, and toilet ownership are indirect factors causing stunting. This study aims to analyze the distribution of stunting incidence and environmental sanitation factors causing stunting in Karo Regency, North Sumatra, Indonesia. A case-control design was conducted on 246 toddlers with a 1:1 ratio. The distribution pattern of stunting incidence and the relationship between patient characteristics and environmental risk factors were studied using a Geographic Information System. Data on clean and healthy living behavior were collected using a questionnaire, and microbiological laboratory tests measured water quality. Spatial analysis used an average nearest-neighbor overlay. The relationship between characteristics and risk factors with stunting incidence was analyzed using chi-square and logistic regression. The average nearest neighbor analysis showed a nearest neighbor index of 0.19 (<1) (Z score -16.72, p-value 0.01). Regression analysis was carried out using GeoDa software (p-value 0.76). There was a relationship between clean water quality, clean and healthy lifestyles (PHBS), and diarrhea (p-value <0.05) and stunting. Family latrines, waste disposal facilities, and wastewater drainage (p-value >0.05) were not associated with stunting. Case distribution tended to be clustered, and no association was found between population density and stunting. This study's findings provide new insights that health promotion to prevent stunting should not only focus on nutritional fulfillment but also on clean and healthy living behaviors and water quality Keywords: Stunting, sanitation, diarrhea, Karo regency, clean water, waste